KINERJA KEUANGAN MEMEDIASI PENGARUH UKURAN PERUSAHAAN, LEVERAGE DAN UKURAN DEWAN KOMISARIS TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Agus Afandi; Andry Sugeng (Universitas Islam Lamongan, 2022)
This study aims to examine the effect of firm size, leverage, and board size on corporate social responsibility (CSR) with financial performance (ROA) as an intervening variable in mining companies in Indonesia. The sample of this research is mining companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The data analysis method used is multiple regression analysis and path analysis. The results showed that (1) firm size had a significant effect on ROA, (2) leverage had no effect on ROA. (3) the size of the board of commissioners has no effect on ROA, (4) the size of the company has no effect on CSR, (5) leverage has a significant effect on CSR, (6) the size of the board of commissioners has no effect on CSR, (7) ROA has a significant effect on CSR